In-Depth Analysis of Photovoltaic-Integrated Shading Systems’ Performance in Residential Buildings: A Prospective of Numerical Techniques Toward Net-Zero Energy Buildings - Ahmad Baghdadi; Maher Abuhussain (Buildings)
The three categories of energy scarcity, population growth and environmental concerns explain the need for new energy sources. Saudi Arabia has become one of the regions capable of using solar energy, particularly through the use of photovoltaic systems, thanks to Saudi Arabia’s excellent ability to effectively utilize the sunlight. This study examines the performance of photovoltaic-integrated shading systems (PVIS) in enhancing energy efficiency for residential buildings under the extreme climatic conditions of Riyadh and Abha in Saudi Arabia. The study advances the knowledge of PVIS applications by addressing the dual challenges of energy efficiency and sustainability in urban residential settings. Leveraging numerical simulations conducted with EnergyPlus, the research evaluates various shading configurations, including louvers, horizontal and sidefin canopies, to quantify their impact on cooling, heating, lighting demands and energy production. The annual efficiency of the proposed integrated systems to achieve sustainable and net-zero energy buildings (NZEBs) is a key metric evaluated in this study. The key findings highlight the effectiveness of horizontal PVIS in achieving the highest energy efficiency, with up to 27.19% in Abha and 24.72% in Riyadh, based on the ratio of annual available solar energy to PV energy production. The integration of PVIS not only reduces the cooling loads by optimizing shading but also contributes significantly to renewable energy production toward NZEBs. The lifecycle cost analysis (LCCA) identifies horizontal canopies as the most cost-effective configuration, with a payback period of 8.6 years in Abha and 10.2 years in Riyadh.